Discontinuation of etanercept after achievement of sustained remission in patients with rheumatoid arthritis who initially had moderate disease activity—results from the ENCOURAGE study, a prospective, international, multicenter randomized study. Issue 5 (2nd September 2016) - Yamanaka, Hisashi; Nagaoka, Shouhei; Lee, Soo-Kon; Bae, Sang-Cheol; Kasama, Tsuyoshi; Kobayashi, Hitomi; Nishioka, Yuichi; Ueki, Yukitaka; Seto, Yohei; Nishinarita, Makoto; Tamura, Naoto; Kimura, Noriko; et al.
Abstract: Objectives : To investigate the efficacy and safety of etanercept (ETN) in patients with rheumatoid arthritis (RA) with moderate disease activity and the possibility to discontinue ETN after achieving remission. Methods : Multicenter, randomized, and open-label study was conducted in Japan and Korea. RA patients (disease duration <5 years) with moderate disease activity despite methotrexate (MTX) treatment were allocated to either MTX or ETN + MTX (Period 1) for 12 months. Patients who achieved sustained remission defined as DAS28 < 2.6 at both 6 and 12 months in the ETN + MTX group, were randomized to either continue or discontinue ETN for 12 months (Period 2). Results : A total of 222 patients were enrolled in Period 1 and clinical remission was achieved in 106/157 (67.5%) and 5/28 (17.9%) patients in the ETN + MTX and MTX groups, respectively. In Period 2, sixty-seven patients were randomized and finally 28/32 (87.5%) and 15/28 (53.6%) patients who continued or discontinued ETN maintained clinical remission. Baseline disease activity and the presence of comorbid diseases influenced the maintenance of remission after ETN discontinuation. Conclusions : ETN + MTX was efficient for RA patients with moderate disease activity into remission. After achieving sustained remission, a half of the patients who discontinued ETN could maintain remission for 1 year.